A new species and record of Bactrocera Macquart (Diptera,Tephritidae) from China - Chen, Xiaolin; Zhou, Libing; Wang, Shaojun; Li, Zhiwen; Li, Jie (Zootaxa, 2011)
One new species of the genus Bactrocera Macquart (Diptera,Tephritidae), B (B.) paradiospyri Chen, Zhou et Li, sp. nov. and one new record species, B (Z.) incisa (Walker, 1861), of this genus from China are described and illustrated. The examined specimens attracted to Cue lure. The type is deposited in Institute of Zoology, Chinese Academy of Sciences, Beijing (IZCAS).